Proposing an alternative allocation algorithm for smartphones: the case of Forall Phones - Alves, Artur Carvalho (2019)
The refurbished market has grown at a considerable pace in recent years. The development of this market is due to the efforts of several countries to move to circular resource consumption that defines a circular economy (Mugge, Jockin, & Bocken, 2017). This is possible by reducing the waste created and reusing materials that would end up in the waste that are used again as resources (European Commission, 2019). This change has been accepted by organizations and their customers who are beginning to see the refurbished market as a great opportunity. Companies see the opportunity to dispose of used product stocks and recover some of their value (Weelden, Bakker, & Mugge, 2016). Customers see the opportunity to buy fully functional products at a fraction of the original price. The development and growth of the refurbished market has been quite noticeable in the smartphone segment, including in Portugal, where Forall Phones has been excelling. It was in the logistics area, in the allocation of smartphones to sales channels, that this project was carried out (a key area for the company's performance), with the aim of improving the allocation of smartphones to sales channels. After mapping the processes, some opportunities for improvement were identified. Then feedback on the approach (designed to respond to opportunities for improvement) was applied and implemented in Excel. The approach was then compared with other approaches being afterwards suggested some recommendations to further improve its performance.